Do beta adrenoceptor blocking agents provide the same degree of clinically convincing morbidity and mortality benefits in patients with chronic heart failure? A literature review - Danaah Malick, Martin Mumuni (Journal of Cardiology and Cardiovascular Medicine, 2019)
Chronic heart failure has been extensively characterized as a disorder arising from a complex interaction between impaired ventricular performance and neurohormonal activation. Since beta adrenoceptor blocking agents are currently considered an integral component of therapy for the management of patients with severe chronic heart failure; several well designed clinical trials have been conducted to determine the morbidity and mortality benefits of these agents these studies, however did not yield the same results in terms of morbidity and mortality benefits. Currently only Bisoprolol, Carvedilol and sustained release metoprolol succinate have clinically proven and convincing morbidity and mortality benefits the current list of approved medicines of the National Health Insurance Scheme (NHIS) of the republic of Ghana does not provide coverage for these lifesaving therapeutic agents. The objective of this review was to collate the relevant scientific evidence that will convince the authorities at the National Health Insurance Authority (NHIA) of the Republic of Ghana to include at least one of the evidence based beta adrenoceptor blocking agents in the list of approved medicines. A thorough search on the internet was conducted using Google scholar to obtain only the clinically relevant studies associated with the benefits of beta adrenoceptor blocking agents in patients with chronic heart failure published in the English language. The phrases beta adrenoceptor blocking agents and chronic heart failure were used as search engines. The search engine yielded several studies that met the predefined inclusion criteria. However, only the Cardiac Insufficiency BIsoprolol Studies (CIBIS-I and CIBIS-II), Carvedilol Prospective Randomized Cumulative Survival Study (COPERNICUS) and Metoprolol CR/XL Randomized Intervention Trial (MERIF-HF) because of the clinical relevance of their findings Beta adrenoceptor blocking agents such as atenolol and propranolol have been used in the management of patients with chronic heart failure. However, their efficacy and optimal dose in reducing mortality have not been scientifically established not all beta adrenoceptor blocking agents scientifically studied provide the same degree of clinically meaningful and convincing morbidity and mortality benefits in patients with chronic heart failure.